Personality qualities versus competitive success rates in elite women's weightlifting sport - Andruchshishin, I. F.; Sivokhin, I. P.; Tolegenova, G.; Ogienko, N. A. (Theory and Practice of Physical Culture, 2019)
Every decision made by an athlete in competitions may have immense effects both for the individual success and the national team standing. A theoretical analysis of the available literature on the subject shows that the personality related issues versus the competitive progress rating studies are still very limited, mostly related to the men's sports or gender-unspecific. The study was designed to rate the personality qualities versus the competitive success rates in the elite women's weightlifting sport. Sampled for the study were elite female weightlifters (n=15) from the national team of Kazakhstan Republic, five of whom are ranked with the top-ten global leaders and the others ranked 20-30ies on the global ranking list. The high-value personality qualities of the sample were found to include anxiety, proneness to domination, high mental control, radicalism, activity, and reactive balancing qualities; and the low-value personality qualities included the thinking pace. It should be emphasized that the middle-weight class was found distinct from the light- and heavyweight classes in the core personality qualities - that may be explained by the higher competitive success rates of the middle-weight athletes.